Design And Development Of Augmented Reality Applications For Human Anatomy Learning Mobile-Based - Ramadhani; Abu Bakar; Rachmad Ikhsan; Wildanil Aufar (LPPM Politeknik Aceh Selatan, 2025)
Human body anatomy is a science that studies the structure of the human body. The anatomy of the human body is composed of cells, tissues, organs and organ systems. Organ systems are the parts that make up the human body. This system consists of various types of organs, which have special structures and functions. Each organ system depends on each other, both directly and indirectly. So far, students have studied body anatomy using books as reference material, making it difficult to explore real objects. Therefore, to make it easier for students to understand the complex anatomy of the body, especially the internal organs of the human body, an Android-based Augmented Reality Book application was developed as a learning media tool. This application makes it easier for students to understand the shape and space of human anatomy using a smartphone. Making this application uses Unity as an application editor, Blender is used to create three-dimensional models and Vuforia as image tracker software